Pathological and virulence markers of two rare Salmonella serovars - Ezzeldeen, Nashwa A.; Ghoniem, Amal A. M.; Osman, A. H. (2002)
Two rarely isolated Salmonella serovars, Solmo- nella Teshie (belonged to Arizona group) and Sal_ monella Ferruch were exmnined for selected viru- lence factors which may be operative in studied serovars including pathogenesis in mice, Congo red binding ability, production of heat-stable enterotoxin. cytotoxin, haemolysin and antibacterial reSistance. The obtained results indicated that oral inoculation of mice with both serovars showed distribution of Salmonella in their different internal organs at different intervals ranging from. 3 hrs up to 9 days post inoculation associated with histopathological changes. Both serovars had Congo red binding activity. S. Ferruch but not S. Teshie produced heat-stable enterotoxin. Both serovars were not cytotoxic to Vero cells. Moreover, both serovars produced (-haemolysin, and had multiple antibacterial resistance.
Includes references.
Summary in Arabic.
1
Keywords: Salmonella infections in animals; Virulence (Microbiology).; Zoonoses